Periodic adhesive contact between an elastic anisotropic layer and a wavy rigid halfspace. (15th August 2016) - To, Quy-Dong; He, Q.-C.; Nguyen, Sy-Tuan; Vu, Minh-Ngoc
Abstract: The paper presents solutions to the periodic adhesive contact problem between an elastic anisotropic layer and a wavy rigid half-space. Different systems including rigid, soft substrate and infinite elastic layer with orientation effect are considered in the paper. The periodic Green function in the form of Fourier series is obtained to formulate an integral equation of the contact pressure. The relation between the contact pressure and the relative approach is derived analytically. The results show that the adhesion effect depends strongly on both material orientation of the elastic layer and the substrate stiffness. These results are in particular useful for the design of new tunable adhesive systems.